Kesetaraan Gender dalam Perspektif Agama di Indonesia - Noverin Andrea Anang; Tjang, Yanto Sandy; Herkulana Mekarryani Soeryamassoka (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Gender equality in the religious sphere in Indonesia is a complex phenomenon, shaped by the interaction between theological doctrines, institutional practices, and the socio-cultural context of each tradition. This study employs a qualitative-descriptive approach through literature review to analyze six major religions in Indonesia: Catholicism, Protestantism, Islam, Hindu Dharma, Buddhism, and Confucianism. The analysis focuses on three main dimensions: theological perspectives regarding gender roles and positions, social changes influencing gender relations, and transformations in institutional structures and practices that support gender equality. The findings indicate that historically, women were often placed in subordinate positions due to patriarchal norms, although the core teachings of these religions contain egalitarian principles and recognition of women’s dignity. Contemporary transformations are reflected in the reinterpretation of religious texts and practices that promote gender equality: Catholicism emphasizes the recognition of women’s dignity within the clerical hierarchy; Protestantism opens opportunities for the ordination of female pastors; Islam reinterprets the principles of Qawwamun and family law rights; Balinese Hindu Dharma adjusts women’s roles in rituals and public spheres; Buddhism revives the bhikkhuni order within the sangha; and Confucianism modernizes the interpretation of Wu Lun and San Cong to emphasize mutual responsibilities between husband and wife. In conclusion, despite persistent patriarchal challenges, this study affirms that religion has the potential to act as an agent of social transformation promoting gender equality while maintaining the moral, spiritual, and traditional values distinctive to each tradition. These findings contribute significantly to academic literature, interfaith dialogue, and the development of more gender-inclusive policies.